Mapping the intangible: The re-semanticisation of the urban landscapes through different spaces of perception. - López-Rodríguez, Silvia; Marín-Clavijo, Jesús; Regosini Jiménez, Stefano (My University, 2023)
This paper deals with the contemporary crisis in urban landscape from a phenomenological point of view, presenting new research perspectives and analytical challenges for urban and landscape stud-ies. This crisis in urban landscape is evident in the mapping of con-temporary urban territories done by architects and urban scholars. These representations do not transmit desires, ideologies, or connota-tions. First, it reviews the understanding of the city as a multiple and a de-centered research object by analyzing the space of perception, which makes possible to discover phenomenological relation of the self with the urban environment, the self-consciousness and self-awareness, and the individual’s mental engagement with ethe city. Second, it proposes research about the urban landscape carried by researchers from the Fine Arts field of study, a re-discovery of the urban spaces that are already known by visual empirical data. The city is discov-ered by individuals who take distance and “look”, individuals who “name” what they see and who “represent” it. Finally, it concludes by discussing some consequences of this exami-nation of the city, especially looking at the qualitative parameters of the urban space and the reassertion of the problem of complexity, especially urban landscape complexity as a point of arrival for these artistic methodologies.
Keywords: Urbanismo - Congresos; City; City as object; Complexity; Perceived environment; Perception; Urban design; Urban planning; Landscape aesthetics; Landscape quality assessment; Social values; Mapping intangible; Landscape perception paradigms